Contribuições à análise estrutural de lajes pré- fabricadas com vigotas treliçadas - Silva, Bernard Rigão da (2012)
Numerical simulations are presented in this work of precast slabs with lattice reinforcement joists with the goal to provide contributions to the structural analysis of this type of slab. An evaluation has been made on the differences between two structural models (isolated beam and grid equivalent) and between two types of analysis (NBR 6118 modified linear analysis and nonlinear analysis with moment-curvature relationships). Applying the grid model equivalent, the influence of the amount of transverse ribbing was also evaluated, especially in deflections checks at Service Limit State. In order to do this, numerical simulations were conducted on precast slabs with lattice reinforcement joists with one, two, three, five and nine transverse ribbing, for each type of analysis. Comparisons of results have enabled several observations, among which stand out the positive effect of the inclusion of transverse ribs, with an average reduction of 29% between the deflections obtained from nonlinear analysis in relation to the modified linear analysis, which is commonly used by designers.